HUBUNGAN DINAMIS ANTARA NILAI TUKAR RUPIAH DAN INFLASI DENGAN INDEKS HARGA SAHAM DI BEI - Vidiyanna Rizal Putri (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2015)
This paper employs the dynamic correlation between the exchange rate and inflation rate on Indonesia Stock Index (IDX). This study provides evidence on the Dynamic Correlation between the exchange rate and inflation rate on Indonesia Stock Index (IDX). This study uses the data from 2011 to 2015 using yearly data. The research method used the Pearson correlation model. The findings indicate that the exchange rate and inflation rate have correlation on Indonesia Stock Index (IDX).